A system dynamics model on reverse logistics profitability of high volume returns with deterioration in computer industry / Roesfiansjah Rasjidin ... [et al.] - Rasjidin, Roesfiansjah; Kuma, Arun; Alam, Firoz; S. Abosuliman, Shougi (Universiti Teknologi MARA, Negeri Sembilan, 2012)
This article presents the dynamic behaviour of five influential factors in computer manufacturer’s reverse logistics (RL) operations, namely part type, return quality, market attractiveness, custom duty percentage and product deterioration rate on its profitability